Literasi digital guru SD Negeri dan SD Swasta: perceived competency dan implementasi - Syafni Nur Afifah; Hasan Mahfud; Roy Ardiansyah (Universitas Sebelas Maret, 2021)
This study explores the difference between public and private school teachers’ self-perceived digital literacy and its implementation in classroom practice. This study only discuss four areas of digital literacy, which consist of devices and software operations, information and data literacy, communication and collaboration, as well as digital content creation. This research used self-reported questionnaires, semi-structured interview, and secondary data gathering to examine teacher’s self-perceived digital literacy and its implementation in classroom practice. The result of this study found that even though there’s no significant difference between public and private school’s teacher self–perceived digital literacy, there are some differences between the implementation of digital literacy in classroom practice. The finding also indicates that even though the teachers did integrate digital literacy in their classroom’s practice, only some pay attention to the cognitive and socio-emotional development of their pupil’s digital literacy.